The immunohistochemical evaluation of the expression of intermediary filaments, pcna, p53 and mmp-9 in feline fibrosarcomas - Emin Karakurt; Ozgur Aksoy; Enver Beytut; Ugur Aydin; Serpil Dag; Ugur Yildiz; Ayfer Yildiz; Ayse Basak Kapcak; Huseyin Koc; Ada Miray Alakan (Eurasian Journal of Veterinary Sciences)
Aim: The present study was aimed at the immunohistochemical evaluation of the expression of cancer indicators; including the Proliferating Cell Nucleus Antigen (PCNA), Matrix Metalloproteinase-9 (MMP-9), vimentin, alphasmooth muscle actin (?-SMA), S-100, desmin and pan-Cytokeratin (Pan- CK), as well as intermediary filaments, with a view to demonstrate the cell proliferation index, p53 tumour-suppressor gene status, tumour metastasis, invasion capacity and cellular origin of feline fibrosarcomas. Materials and Methods: The study material comprised of tumoral tissue samples from 7 cats, which were referred to the Pathology Department for routine histopathological examination. In order to evaluate the histopathological changes, the sections were stained with Haematoxylin and Eosin. Streptavidin-biotin peroxidase complex method was used for immunohistochemical staining. Results: Out of the seven spontaneous cutaneous fibrosarcoma cases, five were in stage I, one was in stage II, and one was in stage III. The presence of conspicuous collagen bands in the tumoral tissues was demonstrated by Masson's trichrome (MT) staining. All cases stained positively for vimentin and ?-SMA. The tumoral cells reacted negatively for pan-CK, S-100 and desmin. All cases were immunopositive for PCNA. Two cases stained positively for p53. These two cases were advanced stage. Only a single case of fibrosarcoma (stage III) presented with intracytoplasmic MMP-9 expression in neoplastic giant cells. Conclusion: Despite only very few tumour samples having been examined in the present study, it was concluded that PCNA, p53 and MMP-9 served as highly useful indicators for determining cell proliferation, grading malignancy, detecting tumour aggressiveness and behaviour, as well as predicting prognosis in spontaneous feline fibrosarcomas.